2020
DOI: 10.35848/1882-0786/ab8728
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth mechanism of high-crystallinity lanthanum hexaboride (001) thin films on silicon (001) by electron beam deposition

Abstract: The growth of high-quality LaB6 thin films on Si(001), by using electron beam deposition, is reported. The films show (001) orientation as confirmed with X-ray diffraction and electron backscattered diffraction (EBSD). The sharp Kikuchi pattern from EBSD evidences a single-crystalline nature of the LaB6(001) films. To accommodate for the lattice mismatch, the LaB6 is azimuthally rotated by 45° with respect to the Si lattice (LaB6[100] ∣∣ Si[110]) and grows in a supercell structure. Early stages of the film gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Beyond this temperature, the possible interdiffusion of B and Si can degrade the crystallinity of LaB 6 . [26] This also agrees with our experimental results obtained at 800 °C, where a lower FOM can be observed when compared to the films deposited at 770 °C. In addition to E-beam evaporation, we attempted to deposit LaB 6 under similar conditions, except for a slower deposition rate through the pulsed laser deposition (PLD) technique, i.e., ≈0.05 Å s −1 (Figures S2 and S3, Supporting Information).…”
Section: Figure 5asupporting
confidence: 92%
See 4 more Smart Citations
“…Beyond this temperature, the possible interdiffusion of B and Si can degrade the crystallinity of LaB 6 . [26] This also agrees with our experimental results obtained at 800 °C, where a lower FOM can be observed when compared to the films deposited at 770 °C. In addition to E-beam evaporation, we attempted to deposit LaB 6 under similar conditions, except for a slower deposition rate through the pulsed laser deposition (PLD) technique, i.e., ≈0.05 Å s −1 (Figures S2 and S3, Supporting Information).…”
Section: Figure 5asupporting
confidence: 92%
“…A separate crystal growth study indicated that this coherence in the crystal orientation is motivated by epitaxial growth with a magic mismatch of the coincidence lattices of LaB 6 and Si(001) surface, which exhibits an in‐plane azimuthal rotation of 45° with respect to each other (LaB 6 [100]||Si [110]). [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations